Transtexual findin meaning of the play "Testament of Bondar Bidakhsh" of Bahram Beyzaei - Shirzad Tayefi; Kourosh Salman Nasr (مطالعات زبانی و بلاغی)
Exploring the meaning of literary works has always been the focus of critics in this field, but the crucial issue is the use of a methodical approach to reach the hidden meanings in different layers of the text. The transtextual approach is a holistic apparatus among literary theories, through which hidden layers of meaning can be discovered. This theory does not have a precise formulation in semantics. However, its elements, from a holistic viewpoint, show special semantic capacities in the syntagmatic and paradigmatic axis of semantic, which have not been investigated so far. For example, hypertext, intertext and metatext work on the paradigmatic axis of semantic. Paratext works on the syntagmatic axis of semantic and architext works both on the syntagmatic and paradigmatic axis of semantic. As such, the interaction of these elements leads to discovering the overall meaning of the text. Therefore, in this research, according to the new perspective of "Transtexual interpretation, it is aimed to analyze y Testament of Bondar Bidakhsh, using qualitative and quantitative analytical methods and relying on library and documentary studies. By applying the theories of transtextuality and semantics to the play, we both seek to formulate a new theoretical apparatus and show the hidden layers of meaning in this play. The results of this analysis show that Beyzaei conveys meaning to the audience through paradigmatic and syntagmatic transtextual elements and transtexual interpretation is an efficient theoretical apparatus to analyze this work.